PSMA PET-CT in Bangladesh: Game Changer in the Management of Prostate Cancer - Mandal, Tapati; Siddique, Md Abu Bakker; Akhter, Papia; Reza, Sharmin; Mutsuddy, Pupree; Begum, Fatima; Bari, A K M Fazlul (Bangladesh Journal of Nuclear Medicine, 2026)
Abstract not available Bangladesh J. Nuclear Med. 29(1): 79-81, 2026